The role of the teacher in construction of informational-educational environment of the school - Шовкун, Віталій Віталійович (ScienceRise: Pedagogical Education, 2016)
The one of basic norms of guaranteeing of formation of competences, necessary for the successful life of pupils in the modern society, is a creation of correspondent informational-educational environment. That is why the important step in realization of the aforesaid educational tendencies within educational institution is a creation of informational-educational environment (IEE) that takes into account the features and needs of the modern generation of pupils. In the article is considered the structure of informational-educational environment of Kherson physical-technical lyceum, its features and functional possibilities for the different participants of educational process with correspondent levels of access. The offered informational-educational environment is permanently improved and added with new modules of software for support of the learning process, automation of the part of processes of the institution management, cooperation with parents